Teaching Strategies and Academic Performance of Students in Basic Science in Oyo State, Nigeria - Ajadi, Olugbenga Timothy; Ayanlowo, Adesoji Emmanuel (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study looks at the basic science teaching methods and academic achievement among junior secondary school students in Oyo State, Nigeria. It focuses on the different approaches used to teach the subject and how these methods affect students' overall academic performance. Methodology: A quantitative approach was used to gather detailed understanding of the respondents on the variables of the study. A validated questionnaire was administered on 450 junior secondary school students by research assistants providing necessary guide when needed. For data analysis, simple percentage was used to identify the strategies for teaching basic science and Pearson Product Moment Correlation was used to establish the relationship between teaching strategies and academic performance of Basic Science students in the study area. Main Findings: The study identified three major strategies that can be used to teach basic science: teacher-centered, interactive, and student-centered. In terms of engagement, teachers engaged the use of teacher-centered and interactive methods due to the prevalent of using these two major strategies but were not using student-centered method to deliver instruction to the students in basic science in the study area. Novelty/Originality of this study: According to the study, teachers' use of instructional tactics can improve students' academic performance, which is a crucial predictor of educational outcomes. It offers insightful information on how basic science functions as a basis for senior secondary school core science courses. Additionally highlighted were the effects of instructional practices on basic science students' academic performance in Oyo State, Nigeria.